2011
DOI: 10.1145/2037661.2037665
|View full text |Cite
|
Sign up to set email alerts
|

Recommendation systems with complex constraints

Abstract: We study the problem of making recommendations when the objects to be recommended must also satisfy constraints or requirements. In particular, we focus on course recommendations: the courses taken by a student must satisfy requirements (e.g., take two out of a set of five math courses) in order for the student to graduate. Our work is done in the context of the CourseRank system, used by students to plan their academic program at Stanford University. Our goal is to recommend to these students courses that not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
112
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(112 citation statements)
references
References 28 publications
0
112
0
Order By: Relevance
“…For example, as AgeRec recommender in Figure 3 is defined based on only one attribute (age), its index is a onedimensional grid based on the age attribute. As this is a continuous domain attribute, each cell represents a range of age values, i.e., [18][19][20][21][22][23][24], [25][26][27][28][29][30][31][32][33][34], and . In the meantime, the AgeCityGenderRec recommender index is a three-dimensional grid based on three attributes (age, city, and gender).…”
Section: B Multi-dimensional Gridmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, as AgeRec recommender in Figure 3 is defined based on only one attribute (age), its index is a onedimensional grid based on the age attribute. As this is a continuous domain attribute, each cell represents a range of age values, i.e., [18][19][20][21][22][23][24], [25][26][27][28][29][30][31][32][33][34], and . In the meantime, the AgeCityGenderRec recommender index is a three-dimensional grid based on three attributes (age, city, and gender).…”
Section: B Multi-dimensional Gridmentioning
confidence: 99%
“…Few, and recent, works have studied the problem of integrating the recommender system functionality with database systems. This includes a framework for expressing flexible recommendation by separating the logical representation of a recommender system from its physical execution [15], [16], algorithms for answering recommendation requests with complex constraints [21], [22], a query language for recommendation [5], and extensible frameworks to define new recommendation algorithms [11], [18], leveraging recommendation for database exploration [10]. Unlike RECATHON, the aforementioned work lacks one or more of the following features: (1) Producing multidimensional recommendation to users, (2) Executing online recommendation queries in a near real time manner, (3) Efficiently initializing and maintaining multiple recommendation algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…Recommender systems are to recommend information items or social elements that are likely to be of interest to users (see [2] for a survey). There has been a host of work on recommender systems [4,10,23,21,28,37], studying item recommendation and package recommendation. Given a query Q, a database D of items and a utility (scoring) function f (·) defined on items, item recommendation is to find top-k items from Q(D) ranked by f (·), for a given positive integer k. Package recommendation takes as additional input a set Σ of compatibility constraints, two functions cost(·) and val(·) defined on sets of items, and a bound C. It is to find top-k packages of items such that each package satisfies the constraints in Σ, its cost does not exceed C, and its val is among the k highest.…”
Section: Related Workmentioning
confidence: 99%
“…There has been work on the complexity of recommendation analyses [23,21,28,37], including our own work [10]. In addition to different settings of the two as remarked earlier, this work differs from the prior work in the following.…”
Section: Related Workmentioning
confidence: 99%
“…In general, we have shown that checking such complex constraints is NP-hard [15]. However, we have identified a sub-class of requirements that in practice is at the core of most actual requirements and that can be checked efficiently.…”
Section: Course Requirementsmentioning
confidence: 99%